Dependence of the recurrence development on the sutures tension force while performance of laparoscopic cruroraphy - V. V. Grubnik; A. I. Tkachenko; V. V. Grubnik (Клінічна хірургія)
Objective. Intraoperative determination of the threads tension force while performance of laparoscopic cruroraphy.